Implementation of the Smart Indonesia Program (PIP) at State Islamic Senior High School (MAN) 3 Balangan - Berkatillah, Akhmad; Anjasmari, Ni Made Musiyani; Budiman, Arif; Sandi, Sandi (LPPM Institut Pendidikan Nusantara Global, 2025)
The Indonesia Smart Program (PIP), as regulated in Minister of Education and Culture Regulation No. 10 of 2020, is a strategic government policy designed to address various challenges in the education sector, including the lack of socialization to parents, mistargeting of aid recipients, a still-centralized determination process, and limited supporting human resources. This study aims to examine the implementation of PIP and the factors influencing it at MAN 3 Balangan, Lampihong District, Balangan Regency, employing a descriptive qualitative approach with a purposive sampling technique involving 12 informants. Data were collected through observation, in-depth interviews, and documentation, and then analyzed through the stages of data reduction, presentation, and conclusion drawing. The findings reveal that the implementation of PIP at MAN 3 Balangan has not been fully optimal, as indicated by weaknesses in actor interests, program benefits, determination structure, technical implementers, and inter-stakeholder coordination. Supporting factors include the availability of facilities, utilization of technology, well-organized administration, and adequate infrastructure, while inhibiting factors consist of limited information, restricted school authority, insufficient socialization, low participation, and uneven understanding among program managers. Therefore, it is recommended that the Ministry of Religious Affairs strengthen socialization, supervision, and coordination, while also encouraging active involvement of school principals, program managers, teachers, parents, and students to enhance the effectiveness of PIP implementation.